Powdered cuxá sauce from Hibiscus sabdariffa L. leaves obtained by foam-mat drying - Cavalcante Neto, Adeval Alexandre [UNESP]; Chaux-Gutiérrez, Ana Maria; Pérez-Monterroza, Ezequiel José [UNESP]; Nagai, Letícia Yuri [UNESP]; Huamaní-Meléndez, Víctor Justiniano [UNESP]; Mauro, Maria Aparecida [UNESP] (Springer Nature, 2025)
Cuxá, a sauce from Roselle (Hibiscus sabdariffa L.) leaves, is a traditional dish in Maranhão, Brazil. This study evaluated foam-mat drying for cuxá powder production using albumin (ALB) and an emulsifier mixture (EMB) as foaming agents. Foam characteristics, density, stability, and overrun were evaluated. The effects of ALB, EMB, and drying temperatures (60, 70, 80 °C) on drying kinetics, color, total phenolic content, and powder morphology were examined. EMB resulted in higher air incorporation compared to ALB. Increased drying temperature led to faster drying times (regardless of foaming agent) and higher effective diffusion coefficients of water (1.12 × 10–9 to 1.97 × 10–9 m2 s−1). ALB influenced cuxá powder color, reducing vividness but maintaining a hue similar to the cuxá sauce for both ALB and EMB powders. Total phenolic content ranged from 4.96 (EMB, 60 °C) to 2.46 mg g−1 (ALB, 80 °C) and decreased with higher temperatures. ALB exhibited superior phenolic compound retention (74.8–71.1%), highlighting its potential for preserving heat-sensitive compounds during drying.
Keywords: Albumin; Color; Diffusion coefficients; Emulsifiers; Phenolic compounds; Proteins